2022
DOI: 10.1002/eat.23793
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between loneliness and disordered eating from early adolescence to adulthood

Abstract: Objective Despite findings from numerous cross‐sectional studies suggesting a substantial association between loneliness and different types of disordered eating, much remains unknown about the impact of confounding, the order of cause and effect, and gender differences in the relationship. Thus, this study followed a large, population‐based, mixed‐gender sample through adolescence and young adulthood, applying a random intercept cross‐lagged panel model (RI‐CLPM) approach to examine the bidirectional prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“… 16 The fifth item, ‘I feel lonely’, assesses loneliness directly. The five-item measure used in this study has been shown to have good face and predictive validity, 10 and has been used in previous longitudinal studies, 17 The reliability of the instrument ranged from α = 0.65 to 0.78 in the present study.…”
Section: Methodsmentioning
confidence: 61%
“… 16 The fifth item, ‘I feel lonely’, assesses loneliness directly. The five-item measure used in this study has been shown to have good face and predictive validity, 10 and has been used in previous longitudinal studies, 17 The reliability of the instrument ranged from α = 0.65 to 0.78 in the present study.…”
Section: Methodsmentioning
confidence: 61%
“…Finally, it will be important to examine the impact of the isolation-induced changes in dopamine signaling for its effects on other outcome measures. For instance, the COVID pandemic has been linked to an increased incidence of eating disorders, such as anorexia nervosa, in adolescent children ( Agostino et al, 2021 ; Devoe et al, 2023 ; Haripersad et al, 2021 ), and it has been established that loneliness and eating disorders are bidirectionally related ( Cortes-Garcia et al, 2022 ). Given our observed link between reward-related feeding behaviors and dopamine changes in the mPFC and NAc during social isolation, it is possible that there is a mechanistic link between the increased incidence of eating disorders stemming from the pandemic lockdowns and lack of social interaction (e.g., home confinement vs. traditional school settings) with dopaminergic dysregulation, a contention that will need to be more fully addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…While chronic social isolation and loneliness have been well established to have a negative impact on physical and mental health, the broad impact of school closures and home confinement during the COVID pandemic brought to the forefront the need to better understand such impacts on the developing brain ( Agostino et al, 2021 ; Cortes-Garcia et al, 2022 ; Hawkley and Cacioppo, 2003 ; Loades et al, 2020 ). Social isolation has been correlated with lower life satisfaction, higher levels of substance abuse, depression, anxiety, and increased stress in humans ( Clair et al, 2021 ; Loades et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research effort has been dedicated to exploring the link between loneliness and eating disorders. For instance, Cortés‐García et al (2022) reported that in their study, social isolation and loneliness significantly predicted disordered eating patterns with particular predominance in male adolescents and young adult women. Feelings of social exclusion and loneliness may also be experienced by those affected by Avoidant Restrictive Food Intake Disorder (ARFID) along with disruptions to functioning due to hospitalisations and medical needs (Görmez et al, 2018).…”
Section: Loneliness Well‐being and Eating Disordersmentioning
confidence: 90%